Isolated Tracks and Media Clouds. - TOBIAS, JAMES (Music, Sound & the Moving Image)
This special volume of Music, Sound, and the Moving Image collects seven broadly ranging essays in the interest of putting problems in, and orientations for, specific lines of research in conversation. Beginning with Nicholas Reyland's work on screen scoring as style in Hollywood blockbusters, and ending with Benjamin Robertson's software studiesoriented critique of media composition, the work collected here stresses the contemporary movement as particularly apposite for staking out problematics, driving questions, and tentative answers across these lines of inquiry. On one hand, massive growth has occurred in scholarship across those fields typically represented in MSMI, while new journals and disciplinary approaches continue to appear; both problems and value proliferate in scholarly work where music and sound meet or inform screen cultures. On the other, recent scholarly handbooks surveying these productively noisy conversations on musicality, sound and audition, and audiovisuality provide, if not a common reference framework, a highly configurable guide to navigating historical and contemporary research at those epistemological inflection points where media studies and cultural and technocultural studies move towards or away from one another and where music, sound, and audiovisual studies becomes ever more vital work.